Populasi dan Intensitas Serangan Hama Kutu Daun (Aphis Gossypii) dan Gejala Penyakit Virus yang Ditimbulkan pada Beberapa Varietas Tanaman Kentang - Muhammad Nur Qoim; Muhammad Sarjan; Hery Haryanto; Ruth Stella Petrunella Thei (Journal of Microbiology, Biotechnology and Conservation, 2026)
Potatoes are a short-lived horticultural crop with a growing period of 90–180 days, depending on the variety, and are a significant source of carbohydrates widely used as vegetables and food ingredients in several countries. Potatoes are best cultivated in highland areas or mountainous regions at altitudes above 700 meters above sea level. Various potato varieties have been developed for export, food industries, and local consumption as vegetables. In Indonesia, common varieties include Atlantik and Chitra, while Mc Russet and Ranger Russet are new industrial varieties under evaluation due to the lack of descriptive data. Superior traits in a potato variety are often associated with reduced incidence and severity of pests and diseases. A study aimed to examine the population and intensity of aphid (Aphis gossypii) infestations and virus symptoms across potato varieties was conducted from April to June 2021 in Sembalun Village, East Lombok Regency, West Nusa Tenggara Province, using a randomized block design (RBD) with four treatments Mc Russet, Ranger Russet, Chitra, and Atlantik each repeated six times, resulting in 24 experimental units. The findings indicated significant differences in pest populations, infestation intensity, and virus symptoms among varieties, with Atlantik having the highest pest population (10 pests/plant) and infestation intensity (2.93%), while Ranger Russet had the lowest (3.42 pests/plant and 1.57%). Virus symptoms were most severe in Chitra (PVY 6.05%, PLRV 5.79%) and least severe in Ranger Russet (PVY 3.19%, PLRV 2.27%).